2006
DOI: 10.1136/bjo.2005.083725
|View full text |Cite
|
Sign up to set email alerts
|

Risks of relapse in patients with acute anterior uveitis

Abstract: Aim: To quantify the rate of recurrence of acute anterior uveitis (AAU), and evaluate the influence of associated risk factors. Methods: We retrospectively reviewed the case notes of 185 patients with acute anterior uveitis, from their time of presentation to August 2001. The time to the first three recurrences of AAU from the onset of the disease was recorded, as well as the site of recurrence. Information regarding risk factors (for example (HLA-B27) status, spondyloarthropathy (SpA), family history of AAU/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…13,15,21,22 The frequency of relapses per year showed no difference between the 2 groups as previous studies found, although some authors reported a higher number of relapses in HLA B27-positive patients and a longer duration of the episodes in HLA B27-negative patients. [12][13][14]23 No statistically significant difference was observed in our groups according to the type and frequency of complications, as already reported by Linssen and Meenken 19 and Tuncer et al 15 Power et al 13 and Rothova 14 showed a higher number of complications in AAU B27-positive patients.…”
supporting
confidence: 82%
“…13,15,21,22 The frequency of relapses per year showed no difference between the 2 groups as previous studies found, although some authors reported a higher number of relapses in HLA B27-positive patients and a longer duration of the episodes in HLA B27-negative patients. [12][13][14]23 No statistically significant difference was observed in our groups according to the type and frequency of complications, as already reported by Linssen and Meenken 19 and Tuncer et al 15 Power et al 13 and Rothova 14 showed a higher number of complications in AAU B27-positive patients.…”
supporting
confidence: 82%
“…However, a detailed analysis revealed that HLA-B27-positive persons with the bilateral form of the disease had a three times smaller risk of recurrence than the HLA-B27-positive patients with unilateral inflammation. In the HLA-B27-negative patients, the relation between recurrences and the form of the disease was similar to the observations by Natkunarajah et al (2007) for all patients with AAU, irrespective of the aetiology of the disease, where a bilateral process promoted relapses. These clinical observations could allow better identification of patients with a higher risk of recurrence of idiopathic AAU.…”
Section: Discussionsupporting
confidence: 83%
“…Patients with chronic autoimmune uveitis are treated until the ocular inflammation is resolved, but it often relapses5. The results of this manuscript suggest that the timing may be important to consider with respect to the induction of regulatory immunity that resists relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Each year 17.6% of active uveitis patients experience a transient or permanent loss of vision, and 12.5% will develop glaucoma4. After an initial episode of anterior uveitis 33% will experience three or more recurrences within 5 years5. The mechanisms contributing to the relapsing and remitting nature of chronic autoimmune uveitis, and how to achieve prolonged remission is unknown.…”
mentioning
confidence: 99%